Advancements in Ayurvedic Researches in the Past 20years-a Database Survey - Dr Gowri M (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Ayurveda is the personalized medicine practiced in India since 200BC. According to WHO 70 – 80% world population rely on nonconventional medicines mainly of herbal sources in their health care. Undoubtedly Ayurvedic treatment stands at par to the conventional medicines in treating the chronic diseases prevalent in the current scenario. Unfortunately due to lack of scientific validation in various concepts, Ayurveda is confronting various challenges which restrain its emergence in the frontier in world wide health scenario. Therefore evidence based research on the basis of advanced research methodology is in high need for the global recognition of the science. Proper research through appropriate Research methodology is the key for validation of a concept. A database survey was conducted on the ayurvedic researches published in the past 20 years using databases like pubmed and NCBI. Evaluation was done regarding the developments and methodologies which have occured so far in these researches in 20 years. In the survey it was observed that there was a progressive development in numbers as well as application and utilization of various research designs in Ayurvedic Research. A changing trend was observed in these 20 years in the research methodologies from preliminary researches like standardization studies in the late 20th century to meta analysis studies in the 2nd decade of 21st century. It was also observed that out of approximately 2000 articles surveyed in total in the time period from 1996 to 2016,using the key words Ayurveda, Research, Ayurvedic Research ,Ayurveda research, only around 323 of them were found to be published by Ayurvedic professionals . The Journals in which these articles were published was also evaluated in reference to scientific journal ranking list and Impact factor and was found that in this sphere too the advancements achieved in the course of time are praiseworthy. It was inferred that though the extent of advancements being achieved in Ayurvedic research, are progressing in the due course of time the number of articles being published in pubmed indexed journal are not in proportion to the works which are actually been conducted in various Ayurvedic Colleges and Research Institutes in India. Thereby due concern should be extended in regard to this issue for the progress of the Science.